2018
DOI: 10.2166/washdev.2018.072
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up rural sanitation in Tanzania: evidence from the National Sanitation Campaign

Abstract: Access to improved sanitation facilities has been a challenge, especially in developing countries. In 2012, Tanzania launched a rural-based National Sanitation Campaign to address the challenge of low coverage of improved sanitation and hygiene at household and school levels using a combination of approaches including Community-Led Total Sanitation (CLTS) and behavior change communication. In June 2016, a study that involved interviews with heads of households, complemented by observations of sanitation and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…The availability of latrine was very high (97.3%), consistent with the reported coverage of 98.3% in Bagamoyo district within Pwani region (27). Our ndings also agrees with those reported in National Sanitation Campaigns where latrine coverage was 94.7% (33) and re-a rm that latrine coverage in Tanzania is high. It was shown that less than a half (43.6%) of households was using improved non shared latrines.…”
Section: Discussionsupporting
confidence: 92%
“…The availability of latrine was very high (97.3%), consistent with the reported coverage of 98.3% in Bagamoyo district within Pwani region (27). Our ndings also agrees with those reported in National Sanitation Campaigns where latrine coverage was 94.7% (33) and re-a rm that latrine coverage in Tanzania is high. It was shown that less than a half (43.6%) of households was using improved non shared latrines.…”
Section: Discussionsupporting
confidence: 92%
“…Initial scoping exercises identified individual contextual factors e.g. leadership (30,31) and monitoring (32,33), and in some case mechanisms for individual types of WASH interventions e.g. community led-total sanitation (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Based on MMAT, eight studies scored 100% [14][15][16][17][18][19][20][21]; ten studies scored 75% [22][23][24][25][26][27][28][29][30][31] and two studies scored 50% [6,32]. With an average MMAT score of 82.5% across the included studies, the studies are considered to be of high quality.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Six studies were conducted in Uganda [6,21,26,28,30,31], two in Ethiopia [18,24], and two in Tanzania [14,20]. Furthemore, one study was conducted in each of the following countries: Zambia [16], Zimbabwe [27], Kenya [23], Nigeria [22], Haiti [19], Malawi [17], Ghana [15] and Sierra Leone ( [32].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation